RUSSIAN LANGUAGE IN THE MODERN WORLD (European Journal of Interdisciplinary Research and Development, 2023)
This article is about the use of the Russian language in the modern world. The Russian language is one of the world (global) languages. This status was given to the language in the 20th century. The spread of the Russian language was largely a consequence of the activities of the Russian Empire and modern Russia. The status of the Russian language was enshrined in the UN, where Russian is one of the six official international languages.